Effectiveness of ISBAR Protocol Implementation by Emergency Medicine Residents in Pediatric Handovers; A Pre-post Intervention Study - Mousaeinejad, Negin; Charmduzi, Forugh; Khosravi, Shaqayeq; Khosravi , Kiana; Jafarnejad, Shabahang; Mahyapourlori , Zahra; Moayedfard, Ahmad; Marashi, Sayed Mahdi (Archives of Academic Emergency Medicine, 2025)
Introduction: Effective information transfer between healthcare providers is essential for patient safety. This study aimed to evaluate the impact of ISBAR (Identify, Situation, Background, Assessment, Recommendation) framework on the quality of clinical handovers in emergency department (ED). Methods: This prospective, pre- and post-intervention study was conducted at Hazrat Ali Asghar Pediatric Hospital in Tehran, Iran, from May to September 2023. A total of 428 clinical handovers were recorded (214 pre-intervention and 214 post-intervention) following a 90-minute training session and the introduction of a standardized ISBAR checklist. Handover quality was measured using the completeness of a 16-item ISBAR checklist. Data analysis employed descriptive statistics, the Mann–Whitney U test, and Chi-square tests. Results: Implementation of the ISBAR protocol significantly improved the overall quality of information conveyed during handovers. Total handover scores increased from a mean rank of 127.55 pre-intervention to 301.45 post-intervention (P < 0.001). All five ISBAR domains showed significant enhancements; Identify (from 145.41 to 283.59, P=0.001), Situation (from 129.64 to 299.36, P=0.001), Background (from 136.40 to 292.60, P=0.001), Assessment (from 156.00 to 273.00, P< 0.001), and Recommendations (from 198.14 to 230.86, P=0.03). In addition, the completeness of individual items such as patient diagnosis, admission date, and vital signs improved markedly. Conclusions: Adopting a standardized ISBAR handover protocol in a high-stakes pediatric environment ED significantly enhances the accuracy and completeness of patient handovers, thereby reducing the potential for errors and strengthening patient safety.